Road Guides and Special Location Monitoring for Blind People Using Ultrasonic Sensors and Microcontroller-Based GPS Modules: Road Guides and Special Location Monitoring for Blind People Using Ultrasonic Sensors and Microcontroller-Based GPS Modules - Pandu Maulana; Ucuk Darusalam; Novi Dian Nathasia (Jurnal Mantik, 2020)
Limitations of blind people in the vision causes them difficulty to perform daily activities. In fact, not infrequently the word about a missing person who is blind majority served in a variety of media today. In this study guide and monitoring tool designed specifically location of the blind using HC-SR04 ultrasonic sensor and is equipped with U-blox GPS Module Neo 6M. HC-SR04 ultrasonic sensor is used to detect an obstacle at a distance of 150 cm. Buzzer detection results will enable the sound output. In monitoring the position, U-blox GPS Module 6M Neo will transmit data such as the coordinates through a cloud platform that can be monitored with the channel location. The test results show that the system of eight variations of distance testing data,